Loop-migration and non-breeding locations of British breeding Wood Warblers Phylloscopus sibilatrix. Issue 1 (3rd April 2022) - Burgess, Malcolm; Castello, Joan; Davis, Tony; Hewson, Chris
ABSTRACT: Capsule: British breeding Wood Warblers Phylloscopus sibilatrix show a clockwise loop migration incorporating stops in southern Europe, the Sahel, and the humid forest zone of West Africa. Aims: To determine autumn and spring migration routes, the location and duration of stopover sites on migration, and the location of non-breeding areas of British breeding Wood Warblers. Methods: In 2016 and 2018 we deployed geolocators to male Wood Warblers on Dartmoor, Devon, and in the New Forest, Hampshire. We retrieved four geolocators from returning birds in 2017, 2019, and 2020. Results: Male Wood Warblers departed breeding sites in late July and stopped for most of August in central southern Europe, crossed the Sahara by a non-stop night and day flight immediately followed by a short stop, and then migrated west to a longer stopover in the Sahel. Final non-breeding destinations were in an area of West Africa covering Guinea, Sierra Leone, and Liberia. Two were tracked on spring migration, again crossing the Sahara via a non-stop flight before migrating through Western Europe to complete a clockwise loop migration back to Britain. Conclusion: All tracked Wood Warblers used stopovers for at least three weeks in three distinct regions, in central southern Europe, in the Sahel, and in the humid zone of West Africa. Although the limitations of geolocation prevent matching locations with habitat, these regions are broadly characterized by distinct forest or woodland habitat types, which differ from breeding habitat. All four tracks showed similar patterns in route, stopover behaviour, and timings, suggesting they may be representative of males in these breeding populations, and potentially of other British and western European Wood Warbler populations.